Cosmopolitanism and the Middle Ages
XIV, 253 p.
Keywords: This collection of essays uncovers a wide array of medieval writings on cosmopolitan ethics and politics, writings generally ignored or glossed over in contemporary discourse. Medieval literary fictions and travel accounts provide us with rich contextualizations of the complexities and contradictions of cosmopolitan thought.